In vivo effects of copper on fish toxicity and cholinesterase of Oreochromis mossambicus (W. K. H. Peters, 1852)(black tilapia) - Basirun, Ain Aqilah (2017)
Heavy metals including copper (Cu) has recently become an overwhelming pollutant towards the environment especially aquatic system. Many current researchers are focusing on cholinesterase (ChE) for biomarker and biosensor development as preliminary screening to prove the existence of xenobiotic in the aquatic system. In this study, an inhibitive assay for Cu was developed using the partially purified fraction of ChE from Oreochromis mossambicus. In addition, the biochemical, morphology and histopathology changes of O. mossambicus were observed as the biomarker for Cu exposure in vivo method. Five selected organs namely brain, blood, gills, liver and muscle depicted the alterations upon 96 h sub-acute exposure of CuSO4. Common anomalies observed include the karyohexis and keryolysis in brain cell strutures, gills hyperplasia, melano macrophage centre (MMC) and hemosiderin formation in liver, blood cell alterations, massive formation of macrophagic cell in blood system and degeneration of muscle bundle in muscle. CuSO4 has also inhibited ChE in in vivo analysis. ChE from five selected organs was inhibited starting from the concentration of 5 mg/L CuSO4. Liver ChE showed the fluctuation of ChE inhibition. In vitro analysis took place where ChE of untreated O. mossambicus was partially purified through affinity chromatography using Procainamide-Sephacryl 6B as ligand. The folds of purification of ChE from brain, blood, gill, liver and muscle ChE were 5.8, 4.9, 3.6, 7.2, and 3.5, respectively. The optimisation of all ChEs were studied. Substrate specificity has specified ChE extracted from all five organs, which are brain (ATC 3.0 mM), blood (PTC 3.0 mM), gill (ATC 2.0 mM), liver (BTC 2.0 mM) and muscle (PTC 2.5 mM). The optimum pH and temperature studies of those organs recorded brain (pH 9, 20°C), blood (pH 9, 40°C), gill (pH 8, 30°C), liver (pH 9, 30°C), and muscle (pH 9, 30°C). In this case, the optimisation of ChEs from five O. mossambicus organs was not much different with each organ. Half maximal inhibitory concentration (IC50) was studied to determine the Cu potency toward inhibiting O. mossambicus ChEs. IC50 of Cu on brain, blood, gill, liver and muscle were 2.65, 0.297, 0.935, 7.66 and 10.58 mg/L. IC50 categorised the blood PrChE of O. mossambicus as very sensitive and suitable to be used as biosensor for Cu pollution monitoring. Those alterations as well as cholinesterase inhibition of fish upon heavy metal exposure can contribute to potential biomarker for aquatic pollution monitoring. Development of biomarker will work as preliminary screening of toxicants prior to second validation through high technology instruments followed by water rehabilitation.